Sleepwalking and Crime: Review with Emphasis on Indian Legal Provisions (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Sleepwalking (somnambulism) is one of the sleep disorders known as the parasomnias, which are basically not disorders of the processes responsible for sleep rather undesirable phenomena that occur predominantly during sleep. It is a disorder of arousal in which the subject arises from deep sleep displaying short and simple behavior or longer complex behavior, including leaving the bed and walking along with memory impairment of the event 1. Eyes are often held open and patients may appear awake during sleepwalking, but motor behavior is usually clumsy and purposeless with slowing in speech and mentation and poor response to stimulation. Noteworthy behavior is that in the entire episode there is no screaming, tremors or autonomic signs such as sweating. Complex behaviors such as cooking, eating and drinking, playing a musical instrument and driving a car may occur during sleepwalking 2, 3. Attempts to wake up patients often do not lead to full arousal and may induce resistance and violence.
Keywords: population; Sleepwalking